Biology, Business and Brain Science: The Strangest of Attractors? - Forbes Jr., Raymond L.; Igonor, Andy; Kuehnl, Kody F. (Advances in Social Sciences Research Journal, 2017)
The fields of biology, business and brain science seem headed down a path toward either collision or convergence. Although neither ordained nor inevitable, the growing interconnections of the three fields, like a snowball going downhill, appear to be currently gaining both momentum and magnitude. The implications of such a coming together are likely to be the subject of intensified debate and controversy among many of the affected parties well into the near-term future. Written from the perspective of practitioners and academics representing each of the three disciplines, this paper employs the concept of “strange attractor” from chaos theory as an integrating feature. This work will discuss several of the salient characteristics and principles existing within the fields of biology, business and brain science. It will also examine the gathering forces moving toward a furthered combination of the disciplines, examine enriched associations between them, and consider possible advantages and disadvantages of their linkages. Additionally, it will explore the possibilities inherent in their greater inter-disciplinary connections as well as peer into the darker side of an enhanced relationship.